RANCANG BANGUN APLIKASI PENGELOLAAN JURNAL ONLINE STUDI KASUS DI STMIK YADIKA BANGIL - Yusron Rijal; Arif Hidayatullah (STMIK YADIKA BANGIL, 2016)
Based on the Decree of the Directorate General of Higher Education (SK Director General of Higher Education) No. 152 / E / T / 2012, concerning provisions of Scientific Journal Publications, the existence of the scientific journal will be one of the graduation requirements for the degree program hierarchy 1. The journal is one of the results of scientific work which is important for the students, so that the journal should be well-organized, effective and efficient. STMIK Yadika is one of the engineering faculty of informatics and information management first in the area Bangil, STMIK Yadika has various support facilities engineering activities informatics and information management, well and computerized,but there is one problem in the management of scientific journals, which is still done manually , this can lead to waste of time, materials and labor, based on the problem, the writer, wanted to make design a newsystem, in the form of management applications online journal, which will be expected to make it easier to manage and publish the results of scientific work that deserves to be published, after carried out the assessment. Based on testing black box testing of the application of this research, that, application management online journal of a case study in STMIK Yadika Bangil, can run well, during the process add, save, edit, delete, or in the process of collecting data and publication of the journal was successful,so as to simplify the process of managing journal in STMIK Yadika Bangil.Keyword : E-Journal, Aplikasi E-Journal, Waterfall Model, Aplikasi Journal Online System